ATHE EFFECT OF MOTIVATION AND TEACHER COMPETENCE ON JOB SATISFACTION BY MODERATION TRANSFORMATION LEADESHIP HEAD MASTER - Aris Hidayanto, 11 52.02 0056 (Students Journal of Economic and Management, 2013)
This research aims to determine whether there is an influence of motivation and competence of teachers on job satisfactions and how the influence of motivation and competence of teachers who moderated the principle transformational leadership on job satisfaction in vocational school in the district of jepara. This research used quantitative descriptive method (explanatory research) it is aimed to test hypothesis on a variable and the correlation of one variable to the other ones in which that hypothesis is received or refused in taking the sampling. The researcher user proportional sampling. It is intended going to balance the proportional of population. The result of this research is: After the data (valid and reliables) were tested with a range of test/hypothesis trhought classical assumption.model test and t test( independent variable partially) a significant positive effect on thedependent variable obtained result :motivation and competence have no effect on job satisfaction ledership transformational has significant and positive effect on job satisfaction.the principal tranfomational leadership did not moderate motivation and competence on job satisfaction. Keyword : Motivation, Teacher Competence, Leadership Transformation, Job Satisfaction Â